2010
DOI: 10.1016/j.ajhg.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Truncating Mutation in SERPINB6 Is Associated with Autosomal-Recessive Nonsyndromic Sensorineural Hearing Loss

Abstract: More than 270 million people worldwide have hearing loss that affects normal communication. Although astonishing progress has been made in the identification of more than 50 genes for deafness during the past decade, the majority of deafness genes are yet to be identified. In this study, we mapped a previously unknown autosomal-recessive nonsyndromic sensorineural hearing loss locus (DFNB91) to chromosome 6p25 in a consanguineous Turkish family. The degree of hearing loss was moderate to severe in affected ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…17 The progressive nature of SNHL, as related to SERPINB6, was proposed even though its progression has not been validated by audiograms in the literature. 17,21 Indeed, subject SB114-206, who carried SERPINB6 mutations in this study, showed significant deterioration of the hearing threshold over 2 years, which was in marked contrast to SB109-201, who possessed OTOGL mutations (Figure 1c). The age at onset of DFNB91-induced SNHL in humans has not been determined previously, but our study clearly indicates that SNHL onset occurred during the early teens, suggesting DFNB91 as a possible etiology of pediatric SNHL.…”
Section: Genetics In Medicine | Volume 17 | Number 11 | November 2015mentioning
confidence: 64%
See 1 more Smart Citation
“…17 The progressive nature of SNHL, as related to SERPINB6, was proposed even though its progression has not been validated by audiograms in the literature. 17,21 Indeed, subject SB114-206, who carried SERPINB6 mutations in this study, showed significant deterioration of the hearing threshold over 2 years, which was in marked contrast to SB109-201, who possessed OTOGL mutations (Figure 1c). The age at onset of DFNB91-induced SNHL in humans has not been determined previously, but our study clearly indicates that SNHL onset occurred during the early teens, suggesting DFNB91 as a possible etiology of pediatric SNHL.…”
Section: Genetics In Medicine | Volume 17 | Number 11 | November 2015mentioning
confidence: 64%
“…11,17 OTOGL is expressed in Claudius cells, Hensen's cells, outer hair cells, and also prominently in the three acellular gelatinous membranes (i.e., the cupula, the otoconical membrane, and the tectorial membrane). OTOGL 17,21 Alterations in this gene do not seem to contribute to congenital, prelingual, severe to profound SNHL based on the absence of mutations in this gene among a large cohort comprising such cases. 17 The progressive nature of SNHL, as related to SERPINB6, was proposed even though its progression has not been validated by audiograms in the literature.…”
Section: Genetics In Medicine | Volume 17 | Number 11 | November 2015mentioning
confidence: 97%
“…This is also evident from three recently identified arNSHI genes, PNPT1, SERPINB6 and TSPEAR, for which mutations have only been described in a single family each. [5][6][7] Further evidence to assign a candidate gene as a deafness gene can come from animal models, especially mouse models with hearing loss. Several genes essential for hearing in humans were identified after they had already been demonstrated to be associated with deafness in mice.…”
Section: Introductionmentioning
confidence: 99%
“…This partial and cell‐specific effect may be due to putative gradients in cochlear expression of DcR1, DcR2, or an unknown TRAIL receptor. Indeed, IHCs and OHCs are known to express different proteins – for example, prestin is expressed in OHCs only (Zheng et al ., 2000) while SERPINB6 is expressed in IHCs only (Sirmaci et al ., 2010). Alternatively, it is possible that the anti‐DR5 antibody could not completely block the function of DR5 due to the complex structure of the multilayered cochlear explants that limited the antibody's access to specific cells.…”
Section: Discussionmentioning
confidence: 99%